1996
DOI: 10.1002/pro.5560050819
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐state NMR studies of the prion protein H1 fragment

Abstract: Conformational changes in the prion protein (PrP) seem to be responsible for prion diseases. We have used conformation-dependent chemical-shift measurements and rotational-resonance distance measurements to analyze the conformation of solid-state peptides lacking long-range order, corresponding to a region of PrP designated H I . This region is predicted to undergo a transformation of secondary structure in generating the infectious form of the protein. Solid-state NMR spectra of specifically '3C-enriched samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
64
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 55 publications
(49 reference statements)
4
64
0
1
Order By: Relevance
“…Taken together, our results underscore the importance of desolvation effects in the relative favorability of α versus β conformations in polypeptides, and serve to emphasize that these effects should be taken into account in modeling [41,43] and in interpreting experimental data on conformational dependence of water-peptide interactions [61]. For example, as mentioned above, some amyloid peptides form β or coil conformations in water but they adopt α-helical conformations in membrane mimicking environments [24]. In light of our model results, a possible scenario is that the desolvation effects are not conducive to helix formation when these peptides are in an aqueous environment.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Taken together, our results underscore the importance of desolvation effects in the relative favorability of α versus β conformations in polypeptides, and serve to emphasize that these effects should be taken into account in modeling [41,43] and in interpreting experimental data on conformational dependence of water-peptide interactions [61]. For example, as mentioned above, some amyloid peptides form β or coil conformations in water but they adopt α-helical conformations in membrane mimicking environments [24]. In light of our model results, a possible scenario is that the desolvation effects are not conducive to helix formation when these peptides are in an aqueous environment.…”
Section: Discussionsupporting
confidence: 65%
“…[59,60] implicated in Parkinson's disease. Explicit solvent simulations and experiments have shown that these sequences assume a large amount of β and coiled conformations in aqueous environments whereas the α helix is their dominant conformational pattern in solvents that mimic the interior of membranes (e.g., hexafluoroisopropanol-water mixture) [23,24,56]. Figure 10 shows how R cutoff affects secondary structure content.…”
Section: Secondary Structures In Amyloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using a structure from this ensemble, we modeled a prion aggregate that agrees with electron microscopy (EM) data from in vitro infectious Syrian hamster and mouse PrP two-dimensional protofibril crystals (24). Other experimental results such as changes in PrP C antibody binding sites (25,26), PrP Sc selective epitopes (27), differential proteinase K digestion (13,28), fiber diffraction (29), solid-state NMR (30)(31)(32), and peptide binding studies of PrP Sc (33)(34)(35) are consistent with our model.…”
mentioning
confidence: 84%
“…Such techniques can also be applied to the structural characterization of amyloid fibrils and other incompletely ordered biological systems. Indeed, site-specific structural measurements have been performed for various amyloidogenic peptides (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and a structural model for fibrils formed by the full length Alzheimer's ␤-amyloid peptide has recently been proposed (24). In this article we report the success of these techniques in permitting the determination of the high-resolution structure of a peptide in an amyloid fibril, elucidating not only the backbone fold but also the precise conformation of the side chains.…”
mentioning
confidence: 99%